Dialog Interreligius-Kultural dan Civil Religion (Studi atas Paguyuban Ngesti Tunggal (Pangestu) - Muryana Muryana (UIN Sunan Kalijaga Yogyakarta, 2013)
The disaster is not only a mere natural occurrence, but also due to the lack of awareness and understanding of one's environmental problems. This paper will review the ecological values contained in the Qur'an. In fact, the Qur'an has given a stern warning of not doing mischief on earth. In this regard, within the certain limits, the query is how religion (Islam) providing ecological value to the whole community through the Koran? Applying semantic-hermeneutical approach, the research results the concept that has been introduced by the Qur'an with various forms and models of word. With some verses that describe the ecological problems, the formulation can be used as 'green religion', namely religion that requires people to practice Islam stressing the integral relationship between faith and the environment (all natural). Moral-ethical action is not only related to human relations, but also with nature.